IMPROVING GRAMMATICAL ACCURACY IN YOUNG EFL LEARNERS - Abdullaeva Gulkhayo Ulugbekovna (Journal of new century innovations, 2023)
Abstract: This article highlights the importance of enhancing grammatical accuracy of the English language in young language learners. It also examines the difficulties which young English language learners encounter while learning English grammar and the ways to develop their accuracy.